(untitled) - Arends, Richard (New York, NY, 2009)
This best-selling text provides comprehensive coverage of general teaching methods and models. The most balanced text in its field, "Learning to Teach" strikes a harmony by integrating its researched-based foundations with practical consideration and opportunity for real world application. The text provides strong coverage of both teacher-centered (Part 3) and student-centered models (Part 4). The eighth edition contains expanded discussions on diversity and differentiation, and new content on constructivist perspectives on research, teaching and learning. By covering all major teaching models plus the leadership skills of teaching, such as planning, classroom management, assessment, motivation, and use/management of time and space, "Learning to Teach" educates future teachers on the theory of successful education as well as the implementation.
Keywords: Teaching,Effective teaching; Textbooks,Textbooks